Memória da migração na Transamazônica na década 1970 - PINTO, Edson Alves (2022)
This paper aims to analyze and understand the migratory process experienced in the municipality of Placas, Baixo Amazonas Mesoregion, belonging to the Microregion of Santarém, in the 1970s. The construction of the trans-Amazonica highway and the migration of colonists were a great repercussion in the television and newspaper. However, to understand this process, we will approach the concepts of colonization as public policies and memory. For the development of this work, a survey was made through bibliographic works of authors who deal with the theme, and data collection was also done through interviews with pioneer settlers, seeking through collective memory and their speeches, knowing what led them to make the decision to migrate to the Amazon, and how they learned about the government's actions for this process. Through this interview, I seek to know about the actions of the government and its agents regarding the fulfillment of public policies in the process of colonization in the trans- Amazonica region. And also gather a series of memories to understand about the mode of survival and the form of social organization adopted by the settlers in the trans-Amazonica region. With this, I also seek to record through the speeches of the pioneers of the transamazonica the result of the migration process and its impact today. Therefore, I hope that this work will be of great value for future research and that new generations can know through the perspectives of those who experience the migratory process as in fact the story happened in this region.